2014
DOI: 10.4238/2014.may.30.5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computed tomography and magnetic resonance imaging in the evaluation of facet tropism and facet arthrosis in degenerative cervical spondylolisthesis

Abstract: ABSTRACT. The aim of this study was to determine the reliability of magnetic resonance imaging (MRI) in the assessment of facet tropism and facet arthrosis of spondylolisthesis levels in degenerative cervical spondylolisthesis as compared to computed tomography (CT). The discrepancies in the interpretation of CT and MRI data in the evaluation of facet tropism and arthrosis have given rise to questions regarding the reliability of comparisons of the two techniques. Using a 4-point scale, 3 blinded readers indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
2
15
1
Order By: Relevance
“…For zygapophyseal osteoarthritis, both the intra- and inter-rater reliability estimates were better than previously reported [ 11 ], which is most likely explained by the use of a dichotomous variable in the current study compared to a classification with four severity categories [ 11 ].…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…For zygapophyseal osteoarthritis, both the intra- and inter-rater reliability estimates were better than previously reported [ 11 ], which is most likely explained by the use of a dichotomous variable in the current study compared to a classification with four severity categories [ 11 ].…”
Section: Discussioncontrasting
confidence: 77%
“…Another limitation is the involvement of only reader A in the intra-rater analysis. Two considerations explain this: 1) previous reliability studies found higher [ 7 9 , 12 , 14 , 21 ] or similar/higher [ 10 , 11 , 13 ] intra-rater reliability than inter-rater reliability and 2) involvement of reader A was necessary since a future prognostic study will involve MRI assessments performed by reader A. As for the inter-rater reliability, the study included three readers, only one of these being a radiologist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) is a useful modality in the assessment of IVDD, since it is highly sensitive to the water content within the tissue [ 3 ]. T2-weighted (T2-WI) and T1-weighted (T1-WI) MRI are the most common techniques to examine the health of intervertebral discs.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we chose multislice CT imaging to examine degenerative changes of the cervical spine. Because reformatted CT images of the spine with bone algorithms is excellent to demonstrate degenerative changes such as reduced height of the intervertebral space, osteophytes, sclerosis of the adjacent cartilaginous endplates, facet joint arthrosis, calcifications and narrowing of the spinal canal [18,19]. Although the grading system for the cervical facet joint arthrosis on CT images were defined in the literature before, in this study we could not find a appropriate grading and scoring system for tomography to compare findings of disc degeneration in both groups.…”
Section: Discussionmentioning
confidence: 99%